Awareness and use of Personal Protective Measures against Mosquito Borne Diseases - Mendhe, Harshal; Bhartendu, Deepshikha; Makade, Kiran; Singh, Daneshwar (Indian Journal of Community Health, 2020)
Background: The key success of Vector Borne Diseases control depends not only on services provided by health authorities but also on awareness of vector borne diseases and community participation. Objectives: The present study was conducted to assess the knowledge and use of PPMs against MBDs in field practice area of UHTC amongst study participants. Methods: It was a community based Cross-sectional study conducted in the field practice area of UHTC among 245 families. Result: 94.7% respondents were aware that malaria is transmitted by mosquito bite. Maximum 102 families were using citronella stick, followed by 98 families using liquid vaporizer. 7.79% participants were using PPM adequately while 3.21 % were using PPM correctly. Conclusion: The general awareness regarding important parameters of mosquito borne diseases was less amongst respondents. Less cost, easy availability and simplicity in using PPM were the reasons cited by the respondents regarding their preferences for choosing PPM.